Optimalisasi Kandungan Serat Kue Kering melalui Substitusi Tepung Beras Hitam dengan Pemberian Isian Pasta Kombinasi Kacang Merah dan Kurma - Damar Maulidina Nur Wening; Annis Catur Adi (Media Gizi Kesmas, 2023)
Background: Optimal consumption of fiber has various benefits, one of which is related to obesity prevention. Out of many attempts to optimize fiber consumption is through the rich-fiber food formulation in the form of cookies. Black rice flour, kidney beans, and dates are the main ingredients chosen according to their nutritional content and benefits. Objectives: The purpose of this study was to analyze the effect of the modification of cookies made from black rice flour and kidney bean-date paste combination within the organoleptic score and fiber content. Methods: The method used in this research is quasi-experimental. Formula treatment was carried out 3 times (F1, F2, F3) along with 1 reference formula (F0). The organoleptic score was known within hedonic test, which involved 32 untrained panelists of women aged 18-40. The fiber content was analyzed empirically through Tabel Komposisi Pangan Indonesia (TKPI) and United States Department of Agriculture (USDA) database. Selected formula was analyzed its crude fiber through gravimetric method at Laboratory of Biochemistry, Nutrition Department, Airlangga University. Results:The highest organoleptic scores of color, aroma, texture, and taste were F1 cookies. Based on empirically analysis, the fiber content between F0 and F4 cookies in 100 g ranges from 2.62 to 9.02 g. Analysis of the crude fiber content of the selected formula, F1 in 100 g is 46.55%. Conclusion: Black rice flour substitute cookies filled with red bean and dates paste combination had a fairly good organoleptic score and appropriate fiber content.